Involvement of microRNA miR‐2b‐3p in regulation of metabolic resistance to insecticides in Plutella xylostella. Issue 4 (24th March 2018) - Etebari, K.; Afrad, M. H.; Tang, B.; Silva, R.; Furlong, M. J.; Asgari, S.
Abstract: The diamondback moth, Plutella xylostella, has developed extremely high levels of resistance to chlorantraniliprole and other classes of insecticides in the field. As microRNAs (miRNAs) play important roles in various biological processes through gene regulation, we examined the miRNA profile of P. xylostella in response to chlorantraniliprole exposure. RNA sequencing analysis showed that insecticide treatment caused significant changes in the abundance of some miRNAs. Increasing exposure time and insecticide concentration induced more dysregulated miRNAs in P. xylostella larvae. We also screened potential target genes for some of the differentially expressed miRNAs (such as miR‐2b‐3p, miR‐14b‐5p and let‐7‐5p), which may play important roles in insecticide resistance development. Exposure of P. xylostella larvae to chlorantraniliprole caused considerable overexpression in the transcript levels of potential target genes cytochrome P450 9f2 ( CYP9F2 ) and 307a1 ( CYP307a1 ). Application of miR‐2b‐3p and miR‐14b‐5p mimics significantly suppressed the relative transcript levels of CYP9F2 and CYP307a1, respectively, in a P. xylostella cell line. Furthermore, enrichment of P. xylostella diet with miR‐2b‐3p mimics significantly increased mortality in deltamethrin‐resistant larvae when exposed to deltamethrin. The results suggest that miR‐2b‐3p may suppress CYP9F2 transcript levels in P. xylostella and consequently inhibit larval detoxification pathways. The findings provide an insight into possible role of miRNAs in regulation of metabolic resistance of insects to insecticides.